[Black Student Union member seated in front of sculpture] (1974)
The BSU member is holding a plant, seated in front of a large head bust sculpture, wearing a light colored sundress and heeled sandals. The BSU member is seated on a large rock, placed in the center of a small garden. Behind them and the large head bust sculpture, there are numerous small trees and bushes.